Experimental heat transfer coefficients between a surface and fixed and fluidized beds with PCM. (5th March 2015) - Izquierdo-Barrientos, M.A.; Sobrino, C.; Almendros-Ibáñez, J.A.
Abstract: This work presents an experimental study to determine the capacity of a phase change material (PCM) in granular form to be used in fixed and bubbling fluidized beds for thermal energy storage. The experimental measurements are focused on determination of the heat transfer coefficient between a heated surface immersed in the bed and the granular PCM. The flow rate is varied to quantify its influence on the heat transfer coefficient. The PCM used is Rubitherm GR50 with a phase change temperature of approximately 50° C. The PCM is available in two different particle sizes, 0.54 mm and 1.64 mm, of which the finer is used in the fluidized bed and the coarser is used in the fixed bed. In addition, the results obtained for the PCM are compared with the heat transfer coefficients measured for sand, a material commonly used for thermal storage. In comparing the heat transfer coefficients for fixed and fluidized beds, the heat transfer coefficients in the fluidized bed with PCM are nearly three times higher than those for the fixed bed at the same gas flow rate. This increase in the heat transfer is a result of two main factors: first, the continuous renewal of PCM particles from the heated surface when they are fluidized, and second, the large quantities of energy in latent form absorbed by the PCM. In the fixed bed there is no renovation of particles, consequently only a small percentage of particles are able to change its phase. Hence, there is no increase in the heat transfer coefficient due to this fact. Highlights: Experimental measurements of the heat transfer rate in fixed and fluidized beds with PCM. No increase in heat transfer coefficient is obtained from the phase change in fixed beds. In a fluidized bed with PCM heat transfer coefficients double due to the phase change.